KOMPOSISI KIMIA DAN SIFAT FUNGSIONAL PATI JAGUNG BERBAGAI VARIETAS YANG DIEKSTRAK DENGAN PELARUT NATRIUM BIKARBONAT - Nur Alam Nur Alam; Nurhaeni Nurhaeni (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The  aim  of  this  experiment  was  to  analyse  chemical  composition  and  functional  properties  of  corn  starch  from various  corn  varieties  extracted  with  natrium  bicarbonat  solution.  Corn  kernels  of  N35,  Sticky  corn,  yellow  Srikandi  and yellow local varieties were processed into starch. The starch was extracted with 1% natrium bicarbonat solution (1:10 [w/v]).  Starch of commercial corn was used as a control. This experiment used Randomized Block Design with three replications. Results of this experiment indicated that the highest starch, amylose, fibre and free fatty acid contents were obtained at starch of yellow local variety; and the highest sugar, protein and lypide contents were found at yellow Srikandi variety, whilst the highest ash content was achieved at N35 variety. Starch of sticky  corn possessed the lowest amylose  content, but had the highest amylopectine content. The highest water absorbtion and solution rate were obtained at starch of yellow local variety.  Furthermore, the highest oil absorbtion rate was achieved at starch of sticky corn variety. Corn starch extracted with natrium bicarbonat solution had a lower quality compared to commercial corn starch, and therefore the corn starch recovered here apparently should not be recommended as a food source.